Design and Implementation MPPT Improved Whale Optimization Algorithm to Overcome Partial Shading Condition on Solar Panel - Habibi, Muhammad Nizar; Prakoso, Rifqi Noviantono; Adila, Ahmad Firyal; Efendi, Moh. Zaenal; Windarko, Novie Ayub; Eviningsih, Rachma Prilian (Universitas Negeri Padang, 2024)
Solar energy is a type of renewable energy whose capacity is tremendous and fast in increasing its capacity so that it can be used for energy sustainability in the future. Solar panels are the only devices that can be used to utilize solar energy. Maximum Power Point Tracking (MPPT) is a method to maximize the power generated by solar panels. However, the problem with solar panels is the condition of partial shading, this occurs due to something blocking the rate of solar irradiation to the solar panel. The result is that there are 2 or more maximum power points from solar panels, the highest power is the Global Maximum Power Point (GMPP) and the other is the Local Maximum Power Point (LMPP). This partial shading condition cannot use conventional MPPT methods due to the complexity of finding GMPP. So, MPPT optimization method is needed, one of which is the Improved Whale Optimization Algorithm (IWOA). IWOA is a development of the Whale Optimization Algorithm (WOA) by applying the Sine-Tent-Cosine Map for the first time the algorithm works to be more effective in the initialization process of the algorithm population and can ensure a more uniform distribution of population distribution throughout the search space. IWOA will be applied to the MPPT system to achieve the GMPP of the solar panel under partial shading conditions.